Hydrogen‐Bonded Polymer–Porphyrin Assemblies in Water: Supramolecular Structures for Light Energy Conversion. Issue 17 (20th July 2017) - Kutz, Anne; Alex, Wiebke; Krieger, Anja; Gröhn, Franziska
Abstract : Making the most of the sunlight: a novel type of functional nanostructure forms by self‐assembly of porphyrins and dendrimeric macromolecules based on hydrogen bonding in aqueous solution. This results in a tunable photosensitizer activity of the porphyrins and improved photocatalysis, promising for solar‐energy conversion. Abstract : In this study, a new type of functional, self‐assembled nanostructure formed from porphyrins and polyamidoamine dendrimers based on hydrogen bonding in an aqueous solution is presented. As the aggregates formed are promising candidates for solar‐energy conversion, their photocatalytic activity is tested using the model reaction of methyl viologen reduction. The self‐assembled structures show significantly increased activity as compared to unassociated porphyrins. Details of interaction forces driving the supramolecular structure formation and regulating catalytic efficiency are fundamentally discussed.